SU(3) symmetry and its breaking effects in semileptonic heavy baryon decays - Xiao-Gang He (Elsevier, 2021)
We employ the flavor SU(3) symmetry to analyze semileptonic decays of anti-triplet charmed baryons (Λc+,Ξc+,0) and find that the experimental data on B(Λc→Λℓ+νℓ) implies B(Ξc0→Ξ−e+νe)=(4.10±0.46)% and B(Ξc0→Ξ−μ+νμ)=(3.98±0.57)%. When this prediction is confronted with recent experimental results from Belle collaboration B(Ξc0→Ξ−e+νe)=(1.31±0.04±0.07±0.38)% and B(Ξc0→Ξ−μ+νμ)=(1.27±0.06±0.10±0.37)%, it is found that the SU(3) symmetry is severely broken. We then consider the generic SU(3) breaking effects both in decay amplitudes and the mixing effect between the anti-triplet and sextet charmed baryons. We find that the pertinent data can be accommodated in different scenarios but the breaking effects are inevitably large. In some interesting scenarios, we also explore the testable implications in these scenarios which can be stringently tested with more data become available. Similar analyses are carried out for the semileptonic decays of anti-triplet beauty baryons to octet baryons and anti-triplet charmed baryons. The validity of SU(3) for these decays can also be examined when data become available.